Pengembangan Media Komedi Buah terhadap Perkembangan Kognitif Anak Usia Dini - Pradani, Dinda Ayu; Izzah, Armiya Nur Lailatul; Lina, Helina Himmatul Ulya (Generasi Emas : Jurnal Pendidikan Islam Anak Usia Dini, 2026)
The development of "Media Komedi Buah" is a fun and interactive learning media for children's cognitive development in group B (aged 5-6 years). The background of the research is based on the low level of children's knowledge about various fruits, which generally still focuses on simple motor activities without providing meaningful experiences. This fruit comedy media product is designed by combining simple and fun concepts for early childhood. The research method used is Research and Development (R&D) with the 4D development model (Define, Design, Develop, Disseminate). The trial subjects were children in group B at the Islamic Plus Khozinatul Ulum Kindergarten in Blora. Data were collected through direct observation at the Islamic Plus Khozinatul Ulum Kindergarten in Blora. The results of the individual trial feasibility included the categories of Strongly Agree and Very Appropriate (100%), small group trials included the categories of Strongly Agree and Very Appropriate (90.5%), field trials included the categories of Strongly Agree and Very Appropriate (92.25%), material experts included the categories of Strongly Agree and Very Appropriate (85.42%), media experts included the categories of Strongly Agree and Very Appropriate (95.37%), and mathematics learning practitioners were in the Strongly Agree and Very Appropriate (92.7%) categories. Based on the assessment results of the six stages, the media komedi buah was declared very suitable for use as a supporting teaching material in children's cognitive development.